1995
DOI: 10.1016/0005-2736(94)00287-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a microsomal subfraction associated with mitochondria of the yeast, Saccharomyces cerevisiae. Involvement in synthesis and import of phospholipids into mitochondria

Abstract: In the yeast, Saccharomyces cerevisiae, similar to higher eukaryotes most phospholipids are synthesized in microsomes. Mitochondria contribute to the cellular biosynthesis of phospholipids insofar as they harbor phosphatidylethanolamine decarboxylase, and enzymes of phosphatidylglycerol and cardiolipin synthesis. In this paper we present evidence that certain enzymes of phospholipid biosynthesis, namely phosphatidylserine and phosphatidylinositol synthase, are enriched in a special microsomal fraction associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
164
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(167 citation statements)
references
References 31 publications
2
164
0
Order By: Relevance
“…In addition, we found a minor part of the immature form of Grx2 associated with membranes of the ER. Interestingly, a connection between mitochondrial and ER membrane systems has been postulated with the existence of the socalled "mitochondrial associated membrane fraction" (53). It remains to be clarified if the localization to ER membranes is a genuine property of Grx2 or due to an association with the mitochondrial associated membrane fraction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found a minor part of the immature form of Grx2 associated with membranes of the ER. Interestingly, a connection between mitochondrial and ER membrane systems has been postulated with the existence of the socalled "mitochondrial associated membrane fraction" (53). It remains to be clarified if the localization to ER membranes is a genuine property of Grx2 or due to an association with the mitochondrial associated membrane fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Most experimental evidence favours membrane contact as the mechanism of transport of PtdSer from MAM, a specialized subfraction of the endoplasmic reticulum, to mitochondria. 1,54,77 As was shown for mammalian MAM, 238 proteolytic treatment of yeast mitochondria negatively affected translocation of PtdSer. 275 Fusogenic proteins similar to those described for mammalian cells by Corazzi's group 33,211 and which are partially inactivated by exogenous proteases, may be involved in this process.…”
Section: Subcellular Location Of Phospholipids Sites Of Synthesis Anmentioning
confidence: 78%
“…Using mammalian cells, Ardail et al [13] demonstrated an interaction of contact sites with a specialized microsomal fraction, which catalyzes synthesis of phospholipids destined for the import into mitochondria. An analogous microsomal fraction, which had been originally described by Vance [14,15] for mammalian cells, was recently also characterized in yeast [16].…”
Section: Introductionmentioning
confidence: 99%